An unusual presentation of left ventricular free wall rupture - Han, Cecelia SY (Pulsus Group Inc, 2010)
Left ventricular free wall rupture (LVFWR) is one of the most lethal complications following myocardial infarction. It accounts for approximately 12% to 21% of all in-hospital deaths following myocardial infarction. The majority of patients die shortly after LVFWR from instantaneous pericardial tamponade and hemodynamic collapse. However, up to one-third of cases are subacute in nature, allowing limited time for emergent surgical repair to prevent sudden death. A high index of suspicion and timely use of diagnostic tests are important in recognizing cases. The present report describes the case of a 69-year-old man who initially presented with acute pericardial tamponade and was subsequently diagnosed with LVFWR in the operating room as the cause of his hemopericardium. The pathology, diagnosis and management of LVFWR are reviewed.